Unusual Presentation of Cystic Papillary Thyroid Carcinoma - Vijayraj S. Patil; Abhishek Vijayakumar; Neelamma Natikar (Case Reports in Endocrinology)
Papillary thyroid carcinoma is the most common thyroid malignancy, accounting for 80% of all thyroid cancers. The most common presentation of thyroid cancer is an asymptomatic thyroid mass or a nodule. Usually as thyroid enlarges, it extends in to mediastinum. Papillary thyroid carcinoma presentation as multiple true cystic swelling extending from neck to anterior chest wall in subcutaneous plane is not present in the literature. We present a rare case of cystic papillary thyroid carcinoma which is presented as subcutaneous swelling with sinus formation.